A neonatal ward-strengthening program improves survival for neonates treated with CPAP at district hospitals in Malawi - Jennifer Carns; Sara Liaghati-Mobarhan; Aba Asibon; Samuel Ngwala; Elizabeth Molyneux; Maria Oden; Rebecca Richards-Kortum; Kondwani Kawaza; Alfred Chalira; Norman Lufesi (Public Library of Science (PLoS), 2022)
From 2013-2015, a CPAP quality improvement program (QIP) was implemented to introduce and monitor CPAP usage and outcomes in the neonatal wards at all government district and central hospitals in Malawi. In 2016 the CPAP QIP was extended into healthcare facilities operated by the Christian Health Association of Malawi. Although clinical outcomes improved, ward assessments indicated that many rural sites lacked other essential equipment and a suitable space to adequately treat sick neonates, which likely limited the impact of improved respiratory care. The aim of this study was to determine if a ward-strengthening program improved outcomes for neonates treated with CPAP. To address the needs identified from ward assessments, a ward-strengthening program was implemented from 2017-2018 at rural hospitals in Malawi to improve the care of sick neonates. The ward-strengthening program included the distribution of a bundle of equipment, supplemental training, and, in some cases, health facility renovations. Survival to discharge was compared for neonates treated with CPAP at 12 rural hospitals for one year before and for one year immediately after implementation of the ward-strengthening program. In the year prior to ward strengthening, 189 neonates were treated with CPAP; in the year after, 232 neonates received CPAP. The overall rate of survival for those treated with CPAP improved from 46.6% to 57.3% after ward strengthening (p = 0.03). For the subset of neonates with admission weights between 1.00-2.49 kg diagnosed with respiratory distress syndrome, survival increased from 39.4% to 60.3% after ward strengthening (p = 0.001). A ward-strengthening program including the distribution of a bundle of equipment, supplemental training, and some health facility renovations, further improved survival among neonates treated with CPAP at district-level hospitals in Malawi.